2016
DOI: 10.1038/ncomms11185
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal homogeneity of driver mutations in diffuse intrinsic pontine glioma

Abstract: Diffuse Intrinsic Pontine Gliomas (DIPGs) are deadly paediatric brain tumours where needle biopsies help guide diagnosis and targeted therapies. To address spatial heterogeneity, here we analyse 134 specimens from various neuroanatomical structures of whole autopsy brains from nine DIPG patients. Evolutionary reconstruction indicates histone 3 (H3) K27M—including H3.2K27M—mutations potentially arise first and are invariably associated with specific, high-fidelity obligate partners throughout the tumour and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
178
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 212 publications
(196 citation statements)
references
References 39 publications
17
178
1
Order By: Relevance
“…K27M-P, K27M-AP and K27M-APP tumor cells were injected into the striatum of NOD-SCID mice, and brains were collected 45–70 days after transplantation. Histopathological analysis revealed that K27M-P, K27M-AP and K27M-APP cells formed 100% diffuse tumors with extensive spreading through striatal, dorsolateral and dorsomedial cortical regions, similar to what is observed in pHGG (Figure 4A and 4B) (Buczkowicz et al, 2014; Louis et al, 2016; Nikbakht et al, 2016). …”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…K27M-P, K27M-AP and K27M-APP tumor cells were injected into the striatum of NOD-SCID mice, and brains were collected 45–70 days after transplantation. Histopathological analysis revealed that K27M-P, K27M-AP and K27M-APP cells formed 100% diffuse tumors with extensive spreading through striatal, dorsolateral and dorsomedial cortical regions, similar to what is observed in pHGG (Figure 4A and 4B) (Buczkowicz et al, 2014; Louis et al, 2016; Nikbakht et al, 2016). …”
Section: Resultssupporting
confidence: 73%
“…H3.3 K27M -tumors and IDH-mutant gliomas possess co-occurring mutations in the same genes (Fontebasso et al, 2014; Khuong-Quang et al, 2012; Nikbakht et al, 2016; Wu et al, 2014). These include alterations affecting the p53 pathway in ~87% of H3.3 K27M tumors (Fontebasso and Jabado, 2015; Fontebasso et al, 2014; Nikbakht et al, 2016) and loss-of-function mutations in ATRX , which occur with increasing frequency in older patients (Fontebasso et al, 2014; Khuong-Quang et al, 2012; Nikbakht et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies may also allow new insights into the processes generating diversity and reveal how constraints to tumor evolution may be exploited, leveraging an adaptive immune response, permitting proactive management of cancers. (Nikbakht et al, 2016); Neuroblastoma (Eleveld et al, 2015); low-grade gliomba/glioblastoma multiforme Kim et al, 2015;Wang et al, 2016); breast cancer (Yates et al, 2015); clear cell renal cell carcinoma (Gerlinger et al, 2014a); multiple myeloma (Bolli et al, 2014); lung adenocarcinomas (de Bruin et al, 2014;Zhang et al, 2014);…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies of the variants above 10% could be explained by variation in neoplastic cell content between FF and FFPE and intra-tumour heterogeneity leading to subclonal alterations. Three of the samples with more striking differences were brain tumours which are well known as highly heterogeneous tumours [42,43].…”
Section: Discussionmentioning
confidence: 99%